Dynamic market power in an exhaustible resource industry: The case of rare earth elements - Frank Pothen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper investigates China's capability to exert power on Rare Earth markets until 2020. A dynamic partial equilibrium model allowing for a disaggregated representation of the mining sector and endogenous investment in capacities is developed. The model is calibrated on a novel dataset on Rare Earth mines. Simulations show that Chinese market power is a transitory phenomenon. In 2014 and 2015, Light Rare Earth prices increase by 21 per cent and Heavy Rare Earth prices more than double compared to free trade, if assuming export restrictions to remain unchanged. Market power on Light Rare Earths vanishes almost completely by 2017 due to the entry of new suppliers, while it persists until 2019 for Heavy Rare Earths. Export restrictions imply a loss of Marshallian welfare of US 1.96 billion outside China. In the short run, even moderate cuts in export quotas can increase exerted market power substantially. Altering tariffs induces smaller but more persistent effects. Sensitivity checks indicate that the results are robust, but delayed opening of new mines and demand shocks can be important for China's capability to exert market power.
urn:nbn:de:bsz:180-madoc-356194
Keywords: F17; Q31; Q37; 330; Partial Equilibrium Model; Metals; Rare Earths; Export Restrictions; Exhaustible Resources